2021
DOI: 10.1101/2021.07.29.21260696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogenesis of Alzheimer’s disease: Involvement of the Choroid Plexus

Abstract: Alzheimer's disease is a neurodegenerative disorder characterized clinically by cognitive decline and pathologically by amyloid deposition and neurofibrillary changes. These neuropathological hallmarks are accompanied by reactive events including microglial activation and astrogliosis. The inflammatory response in Alzheimer's disease brains is distinguished by a pro-inflammatory signature involving amyloid peptides, inflammasome signalling and disrupted blood brain barrier. Inflammatory changes are observed al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…This hypothesis was further explored by considering diagnostic group × CP volume associations. In agreement with previous studies (35)(36)(37), we found larger CP volume at baseline in subjects with dementia, as compared to stable CN (Tables 1B, 2). However, due to our longitudinal study design, we were able to additionally include a group of convertors, which also exhibited a baseline difference from CN, showing further CP increase with cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This hypothesis was further explored by considering diagnostic group × CP volume associations. In agreement with previous studies (35)(36)(37), we found larger CP volume at baseline in subjects with dementia, as compared to stable CN (Tables 1B, 2). However, due to our longitudinal study design, we were able to additionally include a group of convertors, which also exhibited a baseline difference from CN, showing further CP increase with cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
“…CP-mediated neuroinflammation has been suggested as a possible pathophysiological mechanism of AD and other neurodegenerative diseases ( 11 , 12 ) and corroborated by reversal of AD-related cognitive decline and beta-amyloid deposition after introduction of CP targeted immune-suppression ( 38 ). CP inflammation was also linked to increased CP volume and remodeling in AD ( 36 ). Although sex differences in CP immunologic activity in cognitive impairment have to our knowledge not been directly explored, immune mechanisms in AD show significant and complex interactions with sex, with generally, but not exclusively, higher pro-inflammatory activity in females ( 18 , 22 , 23 , 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations